Longitudinal trajectories of subjective care stressors: the role of personal, dyadic, and family resources. (1st February 2019) - Bangerter, Lauren R.; Liu, Yin; Zarit, Steven H.
ABSTRACT: Objectives: Stressors are critical to the caregiver stress process, yet little work has examined resources that contribute to longitudinal changes in subjective stressors. The present study examines a variety of factors that contribute to changes in subjective stressors across time. Method: Dementia caregivers ( N = 153) completed an in-person interview and eight daily telephone interviews at baseline, and follow up interviews at 6 and 12 months. Growth curve analyses examine how care- and non-care stressors, respite, dyadic relationship quality, family support/conflict and care transitions (e.g. nursing home placement) are associated with changes in role overload and role captivity across 12 months. Results: Caregivers who transitioned out of their role had higher overload and captivity at baseline. Among caregivers who transitioned out of caregiving, higher captivity at baseline was associated with declines in captivity and overload; more non-care stressors at baseline was linked to increased captivity and greater overload across time. Adult day service use and family support were associated with lesser captivity over time; taking more breaks from caregiving was linked to lower overload. Higher dyadic relationship quality was associated with lower captivity and overload. Conclusion: Findings contribute to caregiver intervention efforts by highlighting important resources associated with subjective stressors across time.